255 Mirrors trial: minimally invasive robotic surgery, role in optimal debulking ovarian cancer, recovery & survival. (4th December 2020) - Uwins, Christina; Michael, Agnieszka; Tailor, Anil; Chatterjee, Jayanta; Ellis, Patricia; Madhuri, Thumuluru; Skene, Simon; Butler-Manuel, Simon
Abstract : Introduction/Background: MIRRORS is a UK based prospective feasibility study opened June 2020, following ethics approval. Its purpose is to establish the feasibility of launching a randomised control trial (RCT) of Robotic interval debulking surgery for ovarian cancer (including cancer of the fallopian tube & peritoneum) MIRRORS-RCT in the future. MIRRORS will focus on the feasibility of obtaining consent from women and the acceptability of Robotic interval debulking surgery for advanced ovarian cancer. Methodology: Women will be identified through the Gynaecological Oncology multi-disciplinary team meeting. Inclusion Criteria: adult women ≥18 years with stage IIIc–IVb ovarian cancer (including cancer of the fallopian tube & peritoneum) undergoing neo–adjuvant chemotherapy considered suitable for interval debulking surgery (IDS). ≤8 cm pelvic mass on CT Exclusion Criteria: Pelvic Mass >8 cm open surgical approach considered necessary following MDT review. Women lacking capacity to the extent they are unable to understand or complete trial documentation/questionnaires will be excluded from the trial. MIRRORS inclusion criteria are intentionally wide, not restricting by Body Mass Index (BMI), patient comorbidity or Ca125 values. Surgery will commence with an initial laparoscopic assessment followed by a decision to proceed to robotic or open interval debulking surgery. The aim of surgery is to remove all visible disease safely by whichever route. If conversion to open surgery is required to complete this, then it will be done. Results: All women recruited to MIRRORS, whether eventually undergoing robotic or open surgery, will be followed up to assess recovery, complication rate, pain and quality of life. If the following Success Criteria are met, we will progress to MIRRORS-RCT: ≥20% of women eligible for the study accept inclusion in MIRRORS. Robotic IDS Complication rate is not higher than for open interval debulking surgery Conversion to open surgery rate not greater than 50% in patient group deemed suitable for Robotic IDS following initial diagnostic laparoscopy. Conclusion: Robotic surgery is unlikely to be suitable in all cases of ovarian cancer, particularly those with large pelvic masses or extensive disease around the upper part of the abdomen, however, it has the potential to provide significant recovery and quality of life benefits. Ultimately we would like to determine whether, in selected women, robotic surgery offers improved quality of life and recovery with equivalent overall and progression free survival. Disclosures: Anil Tailor: Proctor for Intuitive Surgical Jayanta Chatterjee: paid-lectures on behalf of pharmaceutical companies Agnieszka Michael: Educational-grants: Clovis, GSK, Ipsen, Novartis, Pfizer, and Tesaro Simon Butler-Manuel: Proctor for Intuitive Surgical, Plasma Surgical & Ethicon